Mulheres negras em luta : desintimizando a vida entre alianças clandestinas a partir do campo da socieducação - Cordeiro, Sabrina Ribeiro (2018)
The brasilian estate, compromised with a certain way of governing, promotes mobile divisions between groups that ocuppy diferent places in the social racial hierarchy. Young brasilians have been target from innumerable materializations of a criminal logic that passes through the subjectivation processes in course in the contemporaneity. With legal punitive appliances constitutes around a certain childhood and youth through the last century, is operated a division between potencial ‘value citizens’ on a side, and an horde of future ‘offenders’ in the other, depending on the geografic, social, racial, age localization of the subject. We wach and participate of a control tecnology naturalization scenario and of the association of these govern tactics with the protection and care speech, and the acess to rights in the program and services offer of the social politics. This work was built from an intense experience in the social education policy as a system operator and across other black lives that circulated through these spaces and resisted, inspiring freedom practices in the middle of what constitutes itself as prision and death. The return to the field, in the researcher condition, supported itself on the analytical references and the methodological tools presented by Michel Foucault, Achille Mbembe, Criminal Abolitionism authors, René Lourau, Gilles Deleuze and Félix Guattari. Between the big markers analysis of the policy for one youth, this work incarnates the construction of the criminal logic criticism that permeates the social education system, from a black, female, feminist perspective.